2016
DOI: 10.4140/tcp.n.2016.168
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anticholinergic Medication Use in the Program of All-Inclusive Care for the Elderly

Abstract: PACE participants were prescribed fewer medications and had lower anticholinergic burden, which potentially lowers their risk of adverse effects. These data support the PACE interdisciplinary model by demonstrating the benefit of team care in appropriate use of medications. It provides a potential blueprint to organizations aimed at reducing potentially inappropriate medication prescribing in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…25,32 In populations with mixed cognitive abilities, women were more likely than men to have used a PIM 24,29 or a benzodiazepine, 33 but no association was observed between sex and antipsychotic use. 34 Three of the nine studies 20,25,27,2934 investigating race found racial determinants of PIM use, but the directions differed by the studied population. 25,31,33 Marital status, 26,33 poverty, 26 education, 26,30,31,34 and length of stay 26,28,33 were not significant determinants of PIM use.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…25,32 In populations with mixed cognitive abilities, women were more likely than men to have used a PIM 24,29 or a benzodiazepine, 33 but no association was observed between sex and antipsychotic use. 34 Three of the nine studies 20,25,27,2934 investigating race found racial determinants of PIM use, but the directions differed by the studied population. 25,31,33 Marital status, 26,33 poverty, 26 education, 26,30,31,34 and length of stay 26,28,33 were not significant determinants of PIM use.…”
Section: Resultsmentioning
confidence: 97%
“…18,20,2427,2935 Five studies 25,26,31,33,34 evaluated the relationship between census region and PIM use, with three finding statistically significant differences across regions. 25,31,33 One study of Medicaid recipients in Kentucky found that those living in a nursing home were more likely to receive a PIM than those community-dwellers.…”
Section: Resultsmentioning
confidence: 99%
“…Still, those services would not be using the same clinical decision support systems. It is possible that the effect of MRM could be attenuated when compared against programs with robust clinical pharmacy service offerings [ 46 , 48 , 49 , 50 ]. Finally, we were unable to demonstrate statistically significant differences between groups for their year-over-year change in the proportion of patients with ADEs.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study reveal that SCD should not be considered to be clinically negligible, particularly in older adults under high ACB. In this regard, screening of anticholinergic drugs and calculation of ACB is of importance during routine geriatric assessment visits in older adults with SCD to reduce the development of cognitive impairment and dementia [37]. In addition, it would be helpful to raise awareness about the risk of cognitive impairment and other comorbid conditions due to high ACB among doctors and other health care providers.…”
Section: Discussionmentioning
confidence: 99%